CAP Bench: a benchmark suite for performance and energy evaluation of low‐power many‐core processors - Souza, M.; Penna, Pedro Henrique; Queiroz, Matheus M.; Pereira, Alyson D.; Góes, L. F.; Freitas, H.; Castro, M.; Navaux, P.; Méhaut, Jean-François (Concurrency and Computation: Practice and Experience, 2017)
The constant need for faster and more energy‐efficient processors has been stimulating the development of new architectures, such as low‐power many‐core architectures. Researchers aiming to study these architectures are challenged by peculiar characteristics of some components such as networks‐on‐chip and lack of specific tools to evaluate their performance. In this context, the goal of this paper is to present a benchmark suite to evaluate state‐of‐the‐art low‐power many‐core architectures such as the Kalray MPPA‐256 low‐power processor, which features 256 compute cores in a single chip. The benchmark was designed and used to highlight important aspects and details that need to be considered when developing parallel applications for emerging low‐power many‐core architectures. As a result, this paper demonstrates that the benchmark offers a diverse suite of programs with regard to parallel patterns, job types, communication intensity, and task load strategies suitable for a broad understanding of performance and energy consumption of MPPA‐256 and upcoming many‐core architectures. Copyright © 2016 John Wiley & Sons, Ltd.